Wycena środowiska przyrodniczego z zastosowaniem metody cen hedonicznych - Ligus, Magdalena (Valuing the Natural Environment with the Hedonic Pricing Method, 2006)
The study presents the neoclassical concept of environmental value based on two measures: willing-ness to pay WTP and willingness to accept WTA. These measures correspond to Hicksian compensating variation CV and equivalent variation EV. Twofold depiction of this issue is presented - analytical and graphical in two possible cases: the improvement of environmental quality and deterioration of its condition. Then the analysis of hedonic pricing method for obtaining empirical estimates of environmental values is provided. It seeks to recover estimates of individuals' WTP for environmental quality (usually urban air quality) by observing their behavior in the housing market. First, a hedonic price function is estimated. Then implicit prices are calculated for the environmental variable of interest and a demand curve for this variable may be estimated. Also the short analysis of applicability of WTP and WTA concept is provided.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 84-101